Thermal conductive sheet and method for manufacturing the same
Patent Information
- Application Number
- JP2025059764
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0018】 本発明の熱伝導シートによれば、発熱体と放熱体との間に介在させて使用した際に、温度が上昇した場合であっても発熱体および放熱体との密着状態を良好に維持することができる。
Smart Images

Figure 2026166671000001
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive sheet and a method for manufacturing the thermally conductive sheet.
Background Art
[0002] In recent years, electronic components such as plasma display panels (PDPs) and integrated circuit (IC) chips have seen an increase in heat output as their performance improves. As a result, in electronic devices using the electronic components, it has become necessary to take countermeasures against functional failures caused by temperature rise of the electronic components.
[0003] As a countermeasure against functional failures caused by temperature rise of electronic components, a method is generally adopted in which heat dissipation is promoted by attaching a heat dissipating body such as a metal heat sink, heat dissipation plate, or heat dissipation fin to a heating element such as an electronic component. When using the heat dissipating body, in order to efficiently transfer heat from the heating element to the heat dissipating body, the heating element and the heat dissipating body are brought into close contact with each other with a sheet-shaped member having high thermal conductivity (thermally conductive sheet) interposed therebetween.
[0004] Accordingly, the thermally conductive sheet that is used by being sandwiched between the heating element and the heat dissipating body is required to exhibit excellent thermal conductivity and also allow the heating element and the heat dissipating body to be brought into good close contact with each other.
[0005] Accordingly, for example, Patent Document 1 proposes a thermally conductive sheet that contains at least one type of graphite particles (A) selected from the group consisting of scaly particles, ellipsoidal particles, and rod-shaped particles oriented in the thickness direction, has an elastic modulus of 1.4 MPa or less when the compressive stress at 150°C is 0.1 MPa, and has a tack force of 5.0 N·mm or more at 25°C. The thermally conductive sheet of Patent Document 1 can stably adhere to the heating element and the heat dissipating body, and can ensure heat dissipation performance.
[0006] In addition, as a thermally conductive sheet having excellent adhesion to metals, Patent Document 2 proposes a thermally conductive sheet containing a fluororesin, an acrylic resin with a weight average molecular weight of 20,000 or less, and a thermally conductive filler. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] International Publication No. 2019 / 159340 [Patent Document 2] International Publication No. 2023 / 095758 [Overview of the project] [Problems that the invention aims to solve]
[0008] Here, the heat-generating element and the heat-sinking element are usually made of different materials and have different coefficients of thermal expansion. Therefore, when the temperature of a laminate with a thermal conductive sheet interposed between the heat-generating element and the heat-sinking element rises due to the heat generated by the heat-generating element, the thermal conductive sheet may peel off due to the heat-generating element and the heat-sinking element, which have different coefficients of thermal expansion, warping in different ways, etc., which may cause the thermal conductive sheet to peel off and significantly worsen the thermal resistance.
[0009] Therefore, the conventional thermal conductive sheets described above had room for improvement in that, when used interposed between a heat-generating element and a heat-sinking element, they could maintain good contact with the heat-generating element and the heat-sinking element even when the temperature of the laminate rose due to the heat generated by the heat-generating element.
[0010] Therefore, the present invention aims to provide a heat conductive sheet that, when used interposed between a heat-generating element and a heat-sinking element, can maintain good contact between the heat-generating element and the heat-sinking element even when the temperature rises. [Means for solving the problem]
[0011] The inventors diligently conducted research to achieve the above objective. They then discovered that in a heat-conducting sheet containing a resin and a heat-conducting filler oriented in the sheet thickness direction, if the content ratio of the heat-conducting filler is set to a predetermined value or higher, and a predetermined resin is used as the resin, good adhesion between the heat-generating element and the heat-sinking element can be maintained even when the temperature rises, thus completing the present invention.
[0012] In other words, the present invention aims to advantageously solve the above problems, and [1] the thermal conductive sheet of the present invention is a thermal conductive sheet comprising a resin and a thermal conductive filler, wherein the thermal conductive filler is oriented in the sheet thickness direction, the content ratio of the thermal conductive filler is 35 volume% or more, the resin comprises an acid group-containing resin, and the acid value of the resin is 0.020 mmol / g or more and 0.25 mmol / g or less. In this way, in a thermal conductive sheet comprising a resin and a thermal conductive filler oriented in the sheet thickness direction, if the content ratio of the thermal conductive filler is set to be above the above lower limit and a resin with a predetermined acid value that includes an acid group-containing resin is used, a good state of adhesion with the heating element and heat sink can be maintained even when the temperature rises. In this invention, "orientation in the sheet thickness direction" of the thermal conductive filler means that the orientation angle of the thermal conductive filler is 60° or more and 90° or less with respect to the main surface of the thermal conductive sheet. The "orientation angle" of the thermal conductive filler can be determined by observing the cross-section of the thermal conductive sheet with a scanning electron microscope (SEM), drawing lines along the major axes of 50 arbitrarily selected thermal conductive fillers, and calculating the average value of the angle (acute angle side) of the major axis with respect to the surface of the thermal conductive sheet. Furthermore, in this invention, the "acid value of the resin" can be determined using the method described in the examples.
[0013] Herein, [2] the heat conductive sheet of the present invention is preferably the heat conductive sheet described in [1] above, wherein the acid group-containing resin contains an acid group-containing (meth)acrylic resin. By using an acid group-containing (meth)acrylic resin as the acid group-containing resin, the adhesion to the heat generating element and the heat sink can be further improved. In this invention, "(meth)acrylic" refers to acrylic and / or methacrylic.
[0014] Furthermore, [3] the thermal conductive sheet of the present invention is preferably the thermal conductive sheet described in [1] or [2] above, wherein the acid value of the acid group-containing resin is 0.10 mmol / g or more and 0.35 mmol / g or less. If the acid value of the acid group-containing resin is within the above range, the ability to maintain close contact with the heat-generating element and the heat sink can be further improved. In this invention, the "acid value of the acid group-containing resin" can be determined using the method described in the examples.
[0015] Furthermore, [4] the heat conductive sheet of the present invention is preferably the heat conductive sheet described in any of [1] to [3] above, wherein the resin further contains an acid group-free resin. Including an acid group-free resin further improves the ability to maintain adhesion with the heating element and the heat sink, and also increases the tack strength.
[0016] Furthermore, [5] the thermal conductive sheet of the present invention has a tack force of 50 N / cm 2 More than 100N / cm 2 Preferably, the thermal conductive sheet is one of the following [1] to [4] above. If the tack force is within the above range, it is easy to handle. In this invention, the "tack force" of the thermal conductive sheet can be determined using the method described in the examples.
[0017] Further, the present invention advantageously aims to solve the above problems, and the method for producing a thermally conductive sheet according to the present invention is the method for producing a thermally conductive sheet according to any one of the above [1] to [5], which includes: a pre-thermally conductive sheet forming step of pressurizing a composition containing the resin and the thermally conductive filler to form a sheet shape to obtain a pre-thermally conductive sheet; a laminate forming step of stacking a plurality of the pre-thermally conductive sheets in the thickness direction, or folding or winding the pre-thermally conductive sheet to obtain a laminate; and a slicing step of slicing the laminate at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet. According to such a production method, it is possible to favorably obtain a thermally conductive sheet that can maintain good adhesion to a heating element and a heat radiating element even when the temperature rises.
Advantageous Effects of the Invention
[0018] According to the thermally conductive sheet of the present invention, when used by being interposed between a heating element and a heat radiating element, good adhesion to the heating element and the heat radiating element can be maintained even when the temperature rises.
Modes for Carrying Out the Invention
[0019] Hereinafter, embodiments of the present invention will be described in detail. Each component disclosed in the present embodiment, as well as the preferred aspects, numerical ranges, and respective threshold values defining such numerical ranges indicated for each component, may be independently combined with each other in any aspect.
[0020] Here, the thermally conductive sheet of the present invention can be used by being sandwiched between a heating element such as an electronic component and a heat radiating element such as a metal heat sink, heat radiating plate, or heat radiating fin.
[0021] (Thermally Conductive Sheet) The thermally conductive sheet of the present invention contains a resin and a thermally conductive filler, and optionally further contains an additive. The thermally conductive sheet of the present invention requires that the thermally conductive filler is oriented in the sheet thickness direction, and the content ratio of the thermally conductive filler is 35% by volume or more. Further, the thermally conductive sheet of the present invention requires that the resin includes an acid group-containing resin, and the acid value of the resin is 0.020 mmol / g or more and 0.25 mmol / g or less.
[0022] Further, the thermally conductive sheet of the present invention has the content ratio of the thermally conductive filler set to the above lower limit or more, and uses a resin with a predetermined acid value that contains an acid group-containing resin, so that the good adhesion state with the heating element and the heat radiating body can be maintained even when the temperature rises. Although the reason for this is not clear, it is presumed that the acid groups of the acid group-containing resin interact with the surface of the adherend. It is noted that the acid groups of the acid group-containing resin are presumed to interact particularly favorably when the adherend is made of metal.
[0023] The thermally conductive sheet of the present invention is usually a non-curable sheet that is used as it is without being crosslinked or the like. Therefore, it is preferable that the thermally conductive sheet contains substantially no curing agent such as an epoxy compound. Specifically, the content of the curing agent in the thermally conductive sheet is preferably 1 part by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0 parts by mass, per 100 parts by mass of the resin.
[0024] <Resin> The resin includes an acid group-containing resin, and may optionally further include an acid group-free resin. The acid value of the entire resin is 0.020 mmol / g or more and 0.25 mmol / g or less.
[0025] [Acid group-containing resin] As the acid group-containing resin, a resin having at least one acid group selected from the group consisting of a sulfonic acid group, a phosphoric acid group and a carboxy group can be used. Among these, from the viewpoint of further favorably interacting with the surface of the adherend to further enhance the maintainability of the adhesion state, it is preferable to have a carboxy group as the acid group.
[0026] Here, as the acid group-containing resin, an acid group-containing (meth)acrylic resin is preferred, and a carboxyl group-containing (meth)acrylic resin is more preferred. Furthermore, the acid group-containing (meth)acrylic resin is not particularly limited, and any polymer having acid groups and (meth)acrylic acid ester monomer units can be used. It is preferable that the proportion of (meth)acrylic acid ester monomer units contained in the polymer having acid groups and (meth)acrylic acid ester monomer units is 50% by mass or more.
[0027] A polymer having an acid group and a (meth)acrylic acid ester monomer unit may be obtained (1) by introducing an acid group as a substituent to a polymer that does not have an acid group and has a (meth)acrylic acid ester monomer unit, or (2) a polymer having a (meth)acrylic acid ester monomer unit and an acid group-containing monomer unit. Among these, a polymer having an acid group and a (meth)acrylic acid ester monomer unit is preferred, as is a polymer having a (meth)acrylic acid ester monomer unit and an acid group-containing monomer unit.
[0028] Here, a polymer having (meth)acrylic acid ester monomer units and acid group-containing monomer units can be obtained by polymerizing a monomer composition that includes (meth)acrylic acid ester monomers and acid group-containing monomers, and optionally further includes other monomers. The polymerization method used to prepare the polymer is not particularly limited, and any of the following methods can be used, such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. Among these, emulsion polymerization is preferred. Furthermore, any of the following polymerization reactions can be used, such as ionic polymerization, radical polymerization, and living radical polymerization. In addition, commonly used emulsifiers, dispersants, polymerization initiators, and molecular weight modifiers can be used in the polymerization in general amounts.
[0029] (Meth)acrylic acid ester monomers that can form (meth)acrylic acid ester monomer units are not particularly limited, but include, for example, alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and octyl methacrylate. Examples include alkyl methacrylates such as 2-ethylhexyl methacrylate; alkoxyalkyl acrylates such as methoxymethyl acrylate, ethoxymethyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-propoxyethyl acrylate, 2-butoxyethyl acrylate, 3-methoxypropyl acrylate, and 4-methoxybutyl acrylate; alkoxyalkyl methacrylates such as methoxymethyl methacrylate, ethoxymethyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, 2-propoxyethyl methacrylate, 2-butoxyethyl methacrylate, 3-methoxypropyl methacrylate, and 4-methoxybutyl methacrylate. These may be used individually or in combination of two or more.Among these, alkyl acrylates, alkyl methacrylates, and esters of alkoxyalkyl alcohols having 2 to 12 carbon atoms with (meth)acrylic acid are preferred, alkyl acrylates, alkyl methacrylates, and esters of alkoxyalkyl alcohols having 2 to 8 carbon atoms with (meth)acrylic acid are more preferred, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, n-butyl methylate, 2-ethoxyethyl (meth)acrylate, and 2-methoxyethyl (meth)acrylate are even more preferred, ethyl acrylate, n-butyl acrylate, 2-ethoxyethyl acrylate, and 2-methoxyethyl acrylate are even more preferred, and ethyl acrylate and n-butyl acrylate are particularly preferred.
[0030] Furthermore, when the proportion of total monomer units in the polymer is set to 100% by mass, the proportion of (meth)acrylic acid ester monomer units is preferably 50% by mass or more, more preferably 75% by mass or more, even more preferably 85% by mass or more, particularly preferably 90% by mass or more, preferably 99.9% by mass or less, more preferably 99% by mass or less, and even more preferably 98% by mass or less.
[0031] Acid group-containing monomers that can form acid group-containing monomer units are not particularly limited, but include, for example, monomers having a carboxyl group, monomers having a sulfonic acid group, and monomers having a phosphate group. These may be used individually or in combination of two or more.
[0032] Examples of monomers having a carboxyl group include monocarboxylic acids and their derivatives, dicarboxylic acids and their acid anhydrides, and their derivatives. Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of monocarboxylic acid derivatives include 2-ethyl acrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid. Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Examples of dicarboxylic acid acid anhydrides include maleic anhydride, acrylic anhydride, and methyl maleic anhydride. Examples of dicarboxylic acid derivatives include methyl maleic acid, phenyl maleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and monoesters of dicarboxylic acids. Examples of dicarboxylic acid monoesters include maleic acid monoesters such as monoethyl maleate, monobutyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate; fumarate monoesters such as monomethyl fumarate, monoethyl fumarate, monobutyl fumarate, monocyclopentyl fumarate, and monocyclohexyl fumarate; and itaconic acid monoesters such as monoethyl itaconate and monobutyl itaconate.
[0033] Examples of monomers having a sulfonic acid group include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)acrylic sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylic acid-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-alyloxy-2-hydroxypropanesulfonic acid.
[0034] Examples of monomers containing a phosphate group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In this invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0035] Among those mentioned above, as acid group-containing monomers, monomers having a carboxyl group are preferred, monoesters of monocarboxylic acids and dicarboxylic acids are more preferred, monoesters of acrylic acid, methacrylic acid, and fumarate are even more preferred, and monobutyl acrylic acid and monobutyl fumarate are particularly preferred.
[0036] Furthermore, when the proportion of total monomer units in the polymer is set to 100% by mass, the proportion of acid group-containing monomer units is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, particularly preferably 2% by mass or more, preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less.
[0037] Other monomers that can form other monomer units include, but are not limited to, nitrile group-containing monomers, aromatic vinyl monomers, conjugated diene monomers, (meth)acrylamide monomers, vinyl acetate monomers, and α-olefin monomer units. These can be used individually or in combination of two or more types.
[0038] Here, examples of nitrile group-containing monomers that can form nitrile group-containing monomer units include α,β-ethylenically unsaturated nitrile monomers. Specifically, the α,β-ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, but examples include acrylonitrile; α-halogenoacrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; and α-alkylacrylonitriles such as methacrylonitrile and α-ethylacrylonitrile. Furthermore, examples of aromatic vinyl monomers that can form aromatic vinyl monomer units include styrene, α-methylstyrene, vinyltoluene, and divinylbenzene. Furthermore, examples of conjugated diene monomers that can form conjugated diene monomer units include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, and 2-chlor-1,3-butadiene.
[0039] Furthermore, acrylamide and methacrylamide are examples of (meth)acrylamide monomers that can form (meth)acrylamide monomer units. Furthermore, examples of α-olefin monomers that can form α-olefin monomer units include ethylene, propylene, 1-butene, and 1-hexene.
[0040] Furthermore, when the proportion of all monomer units in the polymer is 100% by mass, the proportion of other monomer units is preferably 25% by mass or less, more preferably 15% by mass or less, and may even be 0% by mass (i.e., the polymer has only (meth)acrylic acid ester monomer units and acid group-containing monomer units).
[0041] Furthermore, the acid group-containing resin described above preferably has a weight-average molecular weight of 300,000 or more, more preferably 400,000 or more, preferably 1,800,000 or less, and more preferably 1,700,000 or less. If the weight-average molecular weight is within the above range, the ability to maintain adhesion to the heat-generating element or heat-sinking element can be further improved. Also, if the weight-average molecular weight is above the lower limit, the adhesive strength to the adherend can be further improved. In this invention, the "weight-average molecular weight" can be measured using the method described in the examples.
[0042] Furthermore, the acid group-containing resin described above preferably has an acid value of 0.05 mmol / g or higher, more preferably 0.10 mmol / g or higher, even more preferably 0.20 mmol / g or higher, preferably 0.50 mmol / g or lower, more preferably 0.40 mmol / g or lower, and even more preferably 0.35 mmol / g or lower. If the acid value of the acid group-containing resin is within the above range, the ability to maintain adhesion to heat-generating elements and heat sinks can be further improved.
[0043] Furthermore, the proportion of acid group-containing resin in the resin may be 100% by mass, but is preferably 10% by mass or more, more preferably 25% by mass or more, preferably 50% by mass or less, and more preferably 35% by mass or less. If the proportion of acid group-containing resin is above the lower limit, the ability to maintain adhesion to the heating element or heat sink can be further improved. Also, if the proportion of acid group-containing resin is below the upper limit, the adhesive strength to the adherend can be further improved.
[0044] [Acid group-free resin] As the acid group-free resin, there are no particular limitations, and hydrocarbon resins, (meth)acrylic resins, nitrile resins, etc., can be used. Here, examples of hydrocarbon resins include polyolefins such as polyisoprene and polybutene; aromatic vinyl-conjugated diene copolymers such as styrene-butadiene copolymer (SBR) and their hydrides; and so on. As the (meth)acrylic resin, there are no particular limitations, and examples include acrylic resins having hydroxyl groups, such as the acrylic resin commercially available from Toagosei Co., Ltd. as the ARUFON® UH-2000 series. Furthermore, as the nitrile resin, there are no particular limitations, and examples include acrylonitrile-butadiene copolymer (NBR) and its hydrides. Among these, from the viewpoint of further improving the adhesive strength to the adherend, polyisoprene, styrene-butadiene copolymer, and acrylic resins having hydroxyl groups are preferred as the acid group-free resin, and acrylic resins having hydroxyl groups are more preferred.
[0045] Here, from the viewpoint of further enhancing the adhesive strength to the adherend, the weight-average molecular weight of the acid-free resin is preferably 1,000 or more and 60,000 or less. Also, from the viewpoint of further enhancing the adhesive strength to the adherend, the glass transition temperature of the acid-free resin is preferably 0°C or lower.
[0046] The proportion of acid-free resin in the resin is not particularly limited, but is preferably 50% by mass or more, more preferably 65% by mass or more, preferably 90% by mass or less, and more preferably 75% by mass or less. If the proportion of acid-free resin is below the above upper limit, the ability to maintain adhesion to the heating element or heat sink can be further improved. Also, if the proportion of acid-free resin is above the above lower limit, the adhesive strength to the adherend can be further improved.
[0047] [Oxidation of resin] Furthermore, the acid value of the resin as a whole is not particularly limited as long as it is between 0.020 mmol / g and 0.25 mmol / g, but is preferably 0.030 mmol / g or higher, more preferably 0.050 mmol / g or higher, even more preferably 0.060 mmol / g or higher, particularly preferably 0.065 mmol / g or higher, preferably 0.20 mmol / g or lower, and more preferably 0.10 mmol / g or lower. If the acid value of the resin is above the lower limit, the ability to maintain adhesion to heat-generating elements and heat sinks can be further improved. Also, if the acid value of the resin is below the upper limit, the adhesive strength to the adherend can be further improved.
[0048] The resin content in the thermal conductive sheet is preferably 65% by volume or less, more preferably 30% by volume or more, more preferably 40% by volume or more, more preferably 63% by volume or less, and more preferably 60% by volume or less. If the resin content is below the above upper limit, the thermal conductivity of the thermal conductive sheet can be further improved. Also, if the resin content is above the above lower limit, the flexibility of the thermal conductive sheet can be ensured, and the ability to maintain close contact with the heat-generating element and heat-sinking element can be further improved.
[0049] <Thermally conductive filler> The thermally conductive filler is oriented in the direction of the sheet thickness. The orientation angle of the thermally conductive filler with respect to the main surface of the thermally conductive sheet is preferably 70° to 90°, and more preferably 80° to 90°. The orientation of the thermally conductive filler in the direction of the sheet thickness allows the thermally conductive sheet to exhibit good thermal conductivity.
[0050] Here, the thermally conductive filler is not particularly limited and includes particulate materials such as alumina particles, zinc oxide particles, boron nitride particles, aluminum nitride particles, silicon nitride particles, silicon carbide particles, magnesium oxide particles, and particulate carbon materials (e.g., graphite and carbon black), as well as fibrous materials such as carbon nanotubes, vapor-grown carbon fibers, carbon fibers obtained by carbonizing organic fibers, and cut pieces thereof. Among these, boron nitride particles and particulate carbon materials are preferred as thermally conductive fillers, boron nitride particles and graphite (e.g., artificial graphite, flake graphite, flaked graphite, natural graphite, acid-treated graphite, expandable graphite, expanded graphite, etc.) are more preferred, and flake-like particulate materials such as boron nitride particles, artificial graphite, flake graphite, expandable graphite, and expanded graphite are even more preferred. By using these thermally conductive fillers, the thermal conductivity of the thermal conductive sheet can be further enhanced. Furthermore, the thermally conductive filler may be used alone or in combination of two or more types.
[0051] Furthermore, the volume-average particle diameter of particulate materials such as particulate carbon materials that can be used as thermally conductive fillers is preferably 10 μm or more and 150 μm or less, and more preferably 30 μm or more and 80 μm or less. If the volume-average particle diameter of the particulate material is below the above upper limit, the surface smoothness of the thermally conductive sheet can be further improved. Also, if the volume-average particle diameter of the particulate material is above the above lower limit, the thermal conductivity of the thermally conductive sheet can be further improved. In this invention, "volume-average particle diameter" refers to the particle diameter at which the cumulative volume calculated from the smallest diameter side accounts for 50% of the particle size distribution (volume-based) measured by laser diffraction, which can be measured in accordance with JIS Z8825.
[0052] Furthermore, the thermal conductive filler content in the thermal conductive sheet must be 35% by volume or more, preferably 37% by volume or more, more preferably 40% by volume or more, preferably 70% by volume or less, and more preferably 60% by volume or less. If the thermal conductive filler content is above the lower limit, the thermal conductivity of the thermal conductive sheet can be further enhanced. Also, if the thermal conductive filler content is below the upper limit, the flexibility of the thermal conductive sheet can be ensured, and the ability to maintain close contact with the heat-generating element and heat-sinking element can be further enhanced.
[0053] Furthermore, when using particulate carbon materials such as graphite as a thermally conductive filler, the content of the thermally conductive filler (particulate carbon material) in the thermally conductive sheet is preferably 37% by volume or more, more preferably 39% by volume or more, preferably 43% by volume or less, and more preferably 41% by volume or less. If the content of particulate carbon material is above the lower limit, the thermal conductivity of the thermally conductive sheet can be further improved. Also, if the content of particulate carbon material is below the upper limit, the flexibility of the thermally conductive sheet can be ensured, and the ability to maintain close contact with the heat-generating element and heat-sinking element can be further improved.
[0054] Furthermore, when boron nitride particles are used as a thermally conductive filler, the content of the thermally conductive filler (boron nitride particles) in the thermally conductive sheet is preferably 50 volume% or more, more preferably 55 volume% or more, preferably 65 volume% or less, and more preferably 63 volume% or less. If the content of boron nitride particles is above the lower limit, the thermal conductivity of the thermally conductive sheet can be further improved. Also, if the content of boron nitride particles is below the upper limit, the flexibility of the thermally conductive sheet can be ensured, and the ability to maintain close contact with the heat-generating element and heat-sinking element can be further improved.
[0055] <Additives> Additives that may be optionally included in the thermal conductive sheet are not particularly limited, but include, for example, flame retardants, plasticizers, toughness modifiers, moisture absorbers, adhesion enhancers, wettability enhancers, and ion trapping agents.
[0056] Furthermore, the proportion of additives in the thermal conductive sheet is not particularly limited and may be 10% by volume or less, 5% by volume or less, 3% by volume or less, or 0% by volume (i.e., the thermal conductive sheet contains no additives).
[0057] <Properties of thermal conductive sheets> Furthermore, the aforementioned thermal conductive sheet has a tack force of 25 N / cm² on the surface (main surface) perpendicular to the thickness direction. 2 Preferably, it is 50 N / cm 2 It is more preferable that the value be greater than or equal to 60 N / cm². 2 It is even more preferable that the value be greater than or equal to 130 N / cm². 2 Preferably, it is 120 N / cm 2 The following is more preferable: If the tack force is above the lower limit, it can be adhered well to the substrate. Also, if the tack force is below the upper limit, it is easy to reposition the adhesive on the substrate.
[0058] Furthermore, while the thickness of the thermal conductive sheet is not particularly limited, it can be, for example, between 30 μm and 600 μm.
[0059] (Method for manufacturing thermal conductive sheets) The thermal conductive sheet of the present invention can be efficiently manufactured by a manufacturing method comprising: (A) a pre-thermal conductive sheet molding step of pressurizing a composition containing a resin and a thermal conductive filler to form a sheet to obtain a pre-thermal conductive sheet; (B) a laminate formation step of stacking multiple pre-thermal conductive sheets in the thickness direction, or folding or winding the pre-thermal conductive sheets to obtain a laminate; and (C) a slicing step of slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermal conductive sheet. The thermal conductive sheet of the present invention may optionally further include steps other than those described in (A) to (C) above.
[0060] <(A) Pre-heat conductive sheet molding process> In the pre-heat-conducting sheet molding process, a composition containing a resin and a heat-conducting filler, and optionally further containing additives, is pressurized and molded into a sheet to obtain a pre-heat-conducting sheet.
[0061] Here, the resin, thermally conductive filler, and additive can be those described above in the "Thermal Conductive Sheet" section. The mixing ratio of the resin, thermally conductive filler, and additive is not particularly limited and can be the ratio described above in the "Thermal Conductive Sheet" section.
[0062] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components can be carried out using known mixing equipment such as a kneader, mixer (e.g., Henschel mixer, Hobart mixer, high-speed mixer), twin-shaft kneader, or rolls, without any particular limitations. The mixing may also be carried out in the presence of a solvent such as ethyl acetate. Alternatively, the resin may be dissolved or dispersed in the solvent beforehand to form a resin solution, which can then be mixed with the thermally conductive filler and any optional additives. The mixing time can be, for example, 5 minutes to 60 minutes. The mixing temperature can be, for example, 5°C to 150°C.
[0063] The composition prepared as described above can be optionally degassed and crushed, and then pressed to form a sheet. A sheet formed by pressing the composition in this way can be used as a pre-heat-conducting sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming the sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.
[0064] Here, the composition can be formed into a sheet using known molding methods such as press molding, rolling molding, or extrusion molding, as long as the molding method involves the application of pressure. In particular, it is preferable to form the composition into a sheet by rolling molding (primary processing).
[0065] Furthermore, in a pre-heat-conductive sheet formed by pressurizing the composition into a sheet, the heat-conductive filler is mainly oriented in the in-plane direction, and it is presumed that the in-plane heat conductivity of the pre-heat-conductive sheet is particularly improved.
[0066] <(B) Laminate formation process> In the laminate formation process, multiple pre-heat conductive sheets obtained in the pre-heat conductive sheet molding process are laminated in the thickness direction, or the pre-heat conductive sheets are folded or wound to obtain a laminate in which multiple pre-heat conductive sheets containing resin and a heat conductive filler are formed in the thickness direction. Here, the formation of the laminate by folding the pre-heat conductive sheets is not particularly limited and can be done by folding the pre-heat conductive sheets to a certain width using a folding machine. Also, the formation of the laminate by winding the pre-heat conductive sheets is not particularly limited and can be done by winding the pre-heat conductive sheets around an axis parallel to the short or long direction of the pre-heat conductive sheets. Furthermore, the formation of the laminate by laminating the pre-heat conductive sheets can be done using a lamination device without particular limitations.
[0067] Furthermore, in laminates obtained by laminating, folding, or winding pre-heat-conductive sheets, it is presumed that the heat-conductive filler is oriented in a direction approximately perpendicular to the lamination direction.
[0068] <(C) Slicing process> In the slicing process, the laminate obtained in the laminate formation process is sliced at an angle of 45° or less with respect to the lamination direction to obtain a heat conductive sheet made of sliced pieces of the laminate. The method of slicing the laminate is not particularly limited and includes, for example, the multi-blade method, laser processing method, water jet method, knife processing method, etc. The cutting tool used when slicing the laminate is not particularly limited and can be a slicing member having a smooth surface with a slit and a blade portion protruding from the slit (for example, a plane or slicer with a sharp blade).
[0069] Furthermore, from the viewpoint of improving the thermal conductivity of the thermal conductive sheet, the slicing angle of the laminate is preferably 30° or less with respect to the lamination direction, more preferably 15° or less with respect to the lamination direction, and preferably approximately 0° with respect to the lamination direction (i.e., in the direction along the lamination direction).
[0070] The heat-conducting sheet obtained in this manner has a structure in which strips containing resin and heat-conducting filler are joined in parallel in the width direction of the strips. Furthermore, in the heat-conducting sheet obtained in this manner, the heat-conducting filler is oriented in the thickness direction of the heat-conducting sheet, resulting in excellent heat conductivity in the thickness direction. Moreover, since the heat-conducting sheet obtained in this manner has a heat-conducting filler content of a predetermined value or higher and uses a resin with a predetermined acid value containing an acid group resin, it can maintain good adhesion with the heat-generating element and heat-sinking element even when the temperature rises. [Examples]
[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" refers to "parts by mass." In addition, in the examples and comparative examples, the acid value and weight-average molecular weight of the resin, as well as the adhesion retention, tack force, and thermal resistance of the thermal conductive sheet, were measured using the following methods.
[0072] <Acid value> [Acid value of acid group-containing resins] The acid value of acid group-containing resins was calculated by weighing approximately 1 g of the resin to be measured, dissolving it in 100 mL of acetone, and performing potentiometric titration with a 0.01 mol / l ethanolic potassium hydroxide solution, using the following formula (X1). A=(Vs-Vb)×0.01×f / Wp...(X1) A: Acid value of acid group-containing resin [mmol / g] Vs: Titration volume of 0.01 mol / l potassium hydroxide solution [mL] Vb: Titration volume of 0.01 mol / l potassium hydroxide solution in a blank without sample [mL] f: Factor of 0.01 mol / l potassium hydroxide solution Wp: Mass of the resin being measured [g] [Acid value of resin] Furthermore, the acid value of the resin contained in the thermal conductive sheet was measured by the following method. First, approximately 1 g of the thermal conductive sheet was weighed, then the weighed sheet was cut into small pieces and immersed in 100 mL of acetone overnight or longer to extract the resin component from the thermal conductive sheet. Next, solid components such as graphite were removed by filtration to obtain a filtrate from which the resin component had been extracted. The filtrate was subjected to potentiometric titration with a 0.01 mol / l ethanolic potassium hydroxide solution. The acid value of the resin was then calculated using the following formula (X2). Note that the solvent is not limited to acetone; any solvent that can dissolve the resin in the thermal conductive sheet and allows for neutralization titration can be used as appropriate, for example, tetrahydrofuran or a toluene / ethanol mixed solvent can also be used. B=(Vs-Vb)×0.01×f / (W0-W1)...(X2) B: Acid value of resin [mmol / g] Vs: Titration volume of 0.01 mol / l potassium hydroxide solution [mL] Vb: Titration volume of 0.01 mol / l potassium hydroxide solution in a blank without sample [mL] f: Factor of 0.01 mol / l potassium hydroxide solution W0: Mass of the thermal conductive sheet before immersion [g] W1: Mass of solids removed by filtration [g] <Weight average molecular weight> The weight-average molecular weight of the resin was measured as a polystyrene equivalent by gel permeation chromatography (GPC). Specifically, a Tosoh HLC-8420 was used as the measuring instrument, two Tosoh TSKgel GMHHR-H columns connected in series were used as the column, and a differential refractometer (Tosoh RI-8420) was used as the detector, under the following conditions. Column size: 7.8mm ID x 30cm Eluent: Tetrahydrofuran Column temperature: 40℃ <Adhesion retention> The adhesion retention of the thermal conductive sheet was evaluated by manufacturing a heat dissipation device as follows. First, a Si wafer (manufactured by Electronics End Materials Corporation, model number: 4'' Si bare wafer, 30mm x 30mm x 0.52mm thick) was prepared as the heat source. Additionally, a copper plate with nickel plating on its surface (30mm long x 30mm wide x 1mm thick) was prepared as a heat sink. Furthermore, the obtained thermal conductive sheet was cut into 15mm x 15mm squares to prepare thermal conductive sheets for heat dissipation devices. Next, a sealant (Dow Corporation, model number: DOWSIL® SE4450) was applied to the perimeter of one side of the heat sink using a dispenser. Next, a pre-cut thermal conductive sheet was placed on top of the heating element, and then the heat sink was placed on top of the thermal conductive sheet so that the side of the heat sink coated with sealant was in contact with the thermal conductive sheet (so that the sealant was on the side facing the heating element). At this time, the approximate center of the heating element in the plane direction, the approximate center of the thermal conductive sheet in the plane direction, and the approximate center of the heat sink in the plane direction were aligned. Next, a pressure jig was prepared, consisting of two opposing pressure plates connected by screws so that they could be brought closer together or further apart. Then, the laminate of the heating element, heat conductive sheet, and heat sink obtained above was set between the pressure plates of the pressure jig, and the torque was adjusted to achieve a surface pressure of 0.3 MPa, and it was fixed with screws. Next, the laminate, fixed with a pressure jig and screws, was heated in a 150°C oven for 1 hour. After heating, it was cooled to room temperature, and the pressure jig and screws were removed. This resulted in a heat dissipation device in which a heating element, a heat conductive sheet, and a heat sink were in close contact in that order. The fabricated heat dissipation device was then measured using an ultrasonic imaging device, FineSAT (FS100III) (manufactured by Hitachi Power Solutions, probe frequency: 25 MHz), and images were acquired. In the obtained images, the areas where the thermal conductive sheet was in close contact with the heat sink and the areas where the thermal conductive sheet had peeled off from the heat sink were determined. The ratio of the area Next, the heat dissipation device was heated in a 150°C oven for 1 hour without load. After heating, the heat dissipation device was cooled to room temperature, and the post-heating adhesion rate (%) was calculated in the same manner as the initial adhesion rate described above. A smaller difference between the initial adhesion rate and the adhesion rate after heating indicates that good adhesion between the heating element and the heat sink can be maintained even when the temperature rises. <Tackiness> The tack force of the thermal conductive sheet was measured using a probe tack tester (manufactured by Resca Co., Ltd., product name "TAC1000"). Specifically, a 4mm diameter heat-conductive sheet was first attached to the tip of a flat, circular probe with a diameter of 5mm using double-sided tape (manufactured by Nichiban Co., Ltd., product name "Nicetack NW-15S"). Next, under an atmosphere of 25°C, the probe with the heat-conductive sheet attached to its tip was pressed against a Si wafer placed on a stage with a load of 1.3N (130gf) for 10 seconds. The force required to pull the probe with the heat-conductive sheet attached away from the Si wafer was then measured. <Thermal resistance value> The thermal resistance of the thermal conductive sheet was measured using a thermal resistance tester (manufactured by Hitachi Technology & Services Co., Ltd., product name: "Resin Material Thermal Resistance Measuring Device"). Specifically, a thermal conductive sheet cut into approximately 1 cm squares was used as the sample, and the thermal resistance value (°C / W) of the thermal conductive sheet was measured under pressures of 0.30 MPa and 0.90 MPa at a sample temperature of 50°C. A smaller thermal resistance value indicates that the thermal conductive sheet has excellent thermal conductivity, and for example, excellent heat dissipation characteristics when interposed between a heat-generating element and a heat-sinking element.
[0073] (Example 1) <Preparation of carboxyl group-containing acrylic resin> A polymerization reactor equipped with a thermometer, stirrer, nitrogen inlet tube, and vacuum device was charged with 200 parts water, 3 parts sodium lauryl sulfate, 33 parts ethyl acrylate and 62 parts n-butyl acrylate as (meth)acrylic acid monomers, and 5 parts mono-n-butyl fumarate as an acid group-containing monomer. After thoroughly removing oxygen from the polymerization reactor by repeatedly degassing under reduced pressure and purging with nitrogen, 0.002 parts sodium formaldehyde sulfoxylate, 0.01 parts dodecyl mercaptan and 0.005 parts cumene hydroperoxide as molecular weight modifiers were added, and the emulsion polymerization reaction was started at atmospheric pressure and room temperature, and the reaction was continued until the polymerization conversion rate reached 95%. The resulting emulsion polymerization solution was solidified with an aqueous magnesium sulfate solution, washed with water, and dried to obtain a carboxyl group-containing acrylic resin (ACM-1) as an acid group-containing resin. The content of mono-n-butyl fumarate units in the obtained carboxyl group-containing acrylic resin (ACM-1) was 5% by mass. The acid value and weight-average molecular weight of the carboxyl group-containing acrylic resin were then measured. The results are shown in Table 1. <Preparation of Composition> Thirty parts of the carboxyl group-containing acrylic resin prepared above, seventy parts of an acrylic resin without acid groups (a hydroxyl group-containing liquid acrylic polymer with a weight-average molecular weight of 6,000 (manufactured by Toagosei Co., Ltd., trade name "ARUFON® UH-2190", weight-average molecular weight: 6,000, glass transition temperature: -47℃)), and 145 parts of expanded graphite as a thermally conductive filler (manufactured by Ito Graphite Industry Co., Ltd., trade name "EC-300", volume-average particle size: 50 μm) were mixed and stirred for 5 minutes using a Hobart mixer (manufactured by Kodaira Seisakusho Co., Ltd., trade name "ACM-5LVT type"). The resulting mixture was degassed under vacuum for 30 minutes to obtain the composition. The obtained composition was then placed in a crusher and crushed for 10 seconds. <Formation of pre-heat-conducting sheet> Next, 1 kg of the crushed composition was sandwiched between 50 μm thick PET film (protective film) that had been sandblasted, and rolled (primary pressurized) under the conditions of a roll gap of 550 μm, roll temperature of 50°C, roll linear pressure of 50 kg / cm, and roll speed of 1 m / min to obtain a pre-heat-conductive sheet with a thickness of 0.5 mm. <Formation of laminates> Next, the obtained pre-heat conductive sheets were cut to 50 mm in length, 50 mm in width, and 0.5 mm in thickness. 120 sheets were stacked in the thickness direction of the pre-heat conductive sheets, and then pressed (secondary pressurized) in the stacking direction at a temperature of 25°C and a pressure of 0.1 MPa for 3 minutes to obtain a laminate with a height of approximately 50 mm. <Formation of a thermally conductive sheet> Subsequently, while pressing the laminated sides of the secondary pressurized laminate with a pressure of 0.3 MPa, a woodworking slicer (manufactured by Marunaka Iron Works Co., Ltd., product name "Super Finishing Planer Super Mecha S") was used to slice the laminate at a 0-degree angle to the lamination direction (in other words, in the direction normal to the main surface of the laminated pre-heat conductive sheet), thereby obtaining a heat conductive sheet measuring 50 mm in length, 50 mm in width, and 0.1 mm in thickness (having a structure in which strips are joined in parallel). The expanded graphite in the heat conductive sheet was oriented in the direction of the sheet thickness. The resulting thermal conductive sheets were then measured and evaluated for adhesion retention, tack force, and thermal resistance. The results are shown in Table 1.
[0074] (Examples 2-7) Except for changing the types and amounts of (meth)acrylic acid ester monomers and acid group-containing monomers, as well as the amounts of dodecyl mercaptan and cumene hydroperoxide, during the preparation of the carboxyl group-containing acrylic resin, the carboxyl group-containing acrylic resin, compositions, pre-heat conductive sheets, laminates, and heat conductive sheets were prepared in the same manner as in Example 1, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0075] (Example 8) During the preparation of the carboxyl group-containing acrylic resin, the amounts of (meth)acrylic acid ester monomer and acid group-containing monomer, as well as the amounts of dodecyl mercaptan and cumene hydroperoxide were changed to obtain carboxyl group-containing acrylic resins with the compositions and weight-average molecular weights shown in Table 1. The carboxyl group-containing acrylic resin, composition, pre-heat-conducting sheet, laminate, and heat-conducting sheet were prepared in the same manner as in Example 1, except that the amount of expanded graphite was changed to 120 parts during composition preparation. Evaluation and measurement were performed in the same manner as in Example 1. The results are shown in Table 1.
[0076] (Example 9) Except for changing the amounts of (meth)acrylic acid ester monomer and acid group-containing monomer, as well as the amounts of dodecyl mercaptan and cumene hydroperoxide, during the preparation of the carboxyl group-containing acrylic resin, the carboxyl group-containing acrylic resin, composition, pre-heat conductive sheet, laminate, and heat conductive sheet were prepared in the same manner as in Example 1, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0077] (Example 10) Except for changing the amount of carboxyl group-containing acrylic resin to 100 parts, omitting the use of acid group-free resin, and changing the amount of expanded graphite to 160 parts during composition preparation, the carboxyl group-containing acrylic resin, composition, pre-heat conductive sheet, laminate, and heat conductive sheet were prepared in the same manner as in Example 2, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0078] (Example 11) Except for changing the types and amounts of (meth)acrylic acid ester monomers and acid group-containing monomers, as well as the amounts of dodecyl mercaptan and cumene hydroperoxide, during the preparation of the carboxyl group-containing acrylic resin, the carboxyl group-containing acrylic resin, compositions, pre-heat conductive sheets, laminates, and heat conductive sheets were prepared in the same manner as in Example 1, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0079] (Example 12) Except for changing the amount of carboxyl group-containing acrylic resin to 40 parts, using 60 parts of polyisoprene (manufactured by Kuraray Co., Ltd., trade name "L-IR-50", weight-average molecular weight: 54,000, glass transition temperature: -63°C) as an acid group-free resin, and changing the amount of expanded graphite to 150 parts, the carboxyl group-containing acrylic resin, composition, pre-thermal conductive sheet, laminate, and thermal conductive sheet were prepared in the same manner as in Example 8, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0080] (Example 13) Except for using 70 parts of styrene-butadiene copolymer (manufactured by Kuraray Co., Ltd., trade name "L-SBR-841N", weight-average molecular weight: 10,000, glass transition temperature: -6°C) as an acid-free resin during composition preparation, and changing the amount of expanded graphite to 150 parts, a carboxyl group-containing acrylic resin, composition, pre-heat-conducting sheet, laminate, and heat-conducting sheet were prepared in the same manner as in Example 8, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0081] (Comparative Example 1) Except for not preparing a carboxyl group-containing acrylic resin and instead using an acrylic resin prepared as described below during composition preparation, the composition, pre-thermal conductive sheet, laminate, and thermal conductive sheet were prepared in the same manner as in Example 1, and evaluated and measured in the same manner as in Example 1. The results are shown in Table 1. <Preparation of acrylic resin> A polymerization reactor equipped with a thermometer, stirrer, nitrogen inlet tube, and vacuum device was charged with 200 parts water, 3 parts sodium lauryl sulfate, 35 parts ethyl acrylate and 65 parts n-butyl acrylate as (meth)acrylic acid monomers. After thoroughly removing oxygen from the polymerization reactor by repeatedly degassing under reduced pressure and purging with nitrogen, 0.002 parts sodium formaldehyde sulfoxylate, 0.01 parts dodecyl mercaptan, and 0.005 parts cumene hydroperoxide were added to initiate an emulsion polymerization reaction at atmospheric pressure and room temperature, and the reaction was continued until the polymerization conversion rate reached 95%. The resulting emulsion polymerization solution was solidified with an aqueous magnesium sulfate solution, washed with water, and dried to obtain an acrylic resin having ethyl acrylate (EA) units and n-butyl acrylate (BA) units.
[0082] (Comparative Example 2) During the preparation of the carboxyl group-containing acrylic resin, the types and amounts of (meth)acrylic acid ester monomers and acid group-containing monomers, as well as the amounts of dodecyl mercaptan and cumene hydroperoxide, were changed to obtain carboxyl group-containing acrylic resins with the compositions and weight-average molecular weights shown in Table 1. In addition, the carboxyl group-containing acrylic resin, composition, pre-heat-conducting sheet, laminate, and heat-conducting sheet were prepared in the same manner as in Example 1, except that the amount of carboxyl group-containing acrylic resin was set to 100 parts, no acid group-free resin was used, and the amount of expanded graphite was changed to 140 parts. Evaluation and measurement were performed in the same manner as in Example 1. The results are shown in Table 1.
[0083] [Table 1]
[0084] Table 1 shows that the thermal conductive sheets of Examples 1 to 13 maintain good adhesion to the heating element and heat sink even after the heat resistance test. On the other hand, Table 1 shows that the thermal conductive sheets of Comparative Example 1, which does not contain acid group-containing resin, and Comparative Example 2, in which the acid value of the resin is above a predetermined value, show a decrease in adhesion to the heating element and heat sink after the heat resistance test. [Industrial applicability]
[0085] According to the heat conductive sheet of the present invention, when used interposed between a heat-generating element and a heat-sinking element, good adhesion between the heat-generating element and the heat-sinking element can be maintained even when the temperature rises.
Claims
1. A thermal conductive sheet comprising a resin and a thermally conductive filler, The aforementioned thermally conductive filler is oriented in the sheet thickness direction, The content ratio of the aforementioned thermally conductive filler is 35% by volume or more. The aforementioned resin includes an acid group-containing resin, A thermal conductive sheet having an acid value of 0.020 mmol / g or more and 0.25 mmol / g or less of the resin.
2. The thermal conductive sheet according to claim 1, wherein the acid group-containing resin includes an acid group-containing (meth)acrylic resin.
3. The thermal conductive sheet according to claim 1, wherein the acid value of the acid group-containing resin is 0.10 mmol / g or more and 0.35 mmol / g or less.
4. The thermal conductive sheet according to claim 1, wherein the resin further comprises an acid group-free resin.
5. Tack force: 50 N / cm 2 More than 100N / cm 2 The thermal conductive sheet according to claim 1, which is as follows:
6. A method for manufacturing a heat conductive sheet according to any one of claims 1 to 5, A pre-heat-conductive sheet molding step involves pressurizing a composition containing the resin and the heat-conductive filler to form a sheet, thereby obtaining a pre-heat-conductive sheet. A laminate formation step is to obtain a laminate by stacking multiple pre-heat conductive sheets in the thickness direction, or by folding or winding the pre-heat conductive sheets. A slicing step in which the laminate is sliced at an angle of 45° or less with respect to the lamination direction to obtain a heat conductive sheet, A method for manufacturing a thermal conductive sheet, including the method described above.
Citation Information
Patent Citations
Heat transfer sheet and heat dissipating device using heat transfer sheet
WO2019159340A1
Heat-conductive sheet
WO2023095758A1